Podnikatelský záměr - Kubešová, Pavlína (Vysoké učení technické v Brně. Fakulta podnikatelská, 2007)
V práci rozhoduji o efektivnosti investičního záměru na základě finanční analýzy, který firma SPAME, s.r.o. hodlá realizovat s rozšířením činnosti. Práce obsahuje analýzu finančního zdraví podniku, zhodnocení ekonomické efektivnosti investice a návrh podnikatelského záměru.

In my thesis I decide on efficiency of investment plan considering the company financial analysis, which the company SPAME Ltd. intends to realize relating to the expansion of its activities. This work contains the analysis of company’s financial health, the evaluation of the economic effectiveness of investments and my recommendation of a business plan.
Business Project
Keywords: Technicko-ekonomická studie; analýza trhu; marketingová strategie; finanční analýza; ekonomická efektivnost investic; rychlý test; Feasibility Study; Analysis of Market; Marketing Strategy; Financial Analysis; Economic Effectiveness of Investment; Quicktest